2021
DOI: 10.29259/jep.v19i1.13111
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Factors Influencing the Labor Productivity of SMEs in South Sumatra

Abstract: This study is to investigate the effect of human capital, labor domicile, gender, and working hours on the productivity of MSME workers in South Sumatra. The data used are primary data, data collection with a purposive sample approach as many as 196 samples as workers in SMEs. This study applies a logistic regression approach. The findings of this study indicate that independent tests, human capital, labor domicile, gender, and working hours have a significant relationship to labor productivity. Likewise, join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
1
4
0
3
Order By: Relevance
“…The model is statistically significant by Fisher's and Student's tests, R-squared value (99.6662) and P-Value (0.000) (Tables 1 and 2). Table 1 shows the obtained coefficients of the regression model (5) and the verification of its statistical significance using the Student's test, the standard error, and the P-value. The tabular value of the Student's criterion for 35 variables is 2.030 at a significance level of P-Value of 5%, the obtained values for K2 = -5.0827, K4 = 10.0419, K6 = 8.8626.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model is statistically significant by Fisher's and Student's tests, R-squared value (99.6662) and P-Value (0.000) (Tables 1 and 2). Table 1 shows the obtained coefficients of the regression model (5) and the verification of its statistical significance using the Student's test, the standard error, and the P-value. The tabular value of the Student's criterion for 35 variables is 2.030 at a significance level of P-Value of 5%, the obtained values for K2 = -5.0827, K4 = 10.0419, K6 = 8.8626.…”
Section: Resultsmentioning
confidence: 99%
“…Gardner et al (2023) considered how international trade indicators affect labor productivity; the calculation was carried out using statistical methods. Atiyatna et al (2021) applied the logistic regression method to search for factors influencing labor productivity and found that human capital, place of residence, gender, and working hours significantly affect labor productivity indicators. Such variables most often include the workforce's qualification level, the quality of the working environment, the availability of opportunities for further training, and access to modern technologies and the latest equipment (Sotnyk, 2012;Sheliemina, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…biaya tenaga kerja, sewa gedung. Sedangkan biaya implisit disebut juga imputed cost (ongkos tersembunyi), ialah taksiran biaya atas faktor produksi yang dimiliki sendiri oleh perusahaan dan ikut digunakan dalam proses produksi yang dimiliki oleh perusahaan, e.g., penggunaan gedung milik perusahaan sendiri (Atiyatna et al, 2021).…”
Section: Biaya Produksiunclassified
“…Rendahnya kinerja yang dihasilkan UMKM di Indonesia disebabkan rendahnya kualitas SDM (Susilo, 2010). Hal ini ditunjukkan dengan masih rendahnya pengembangan dan penguasaan ilmu pelaku UMKM dibidang manajemen, organisasi, teknologi, pemasaran dan kompetensi lainnya yang diperlukan dalam mengelola usaha (Atiyatna et al, 2021).…”
Section: Pendahuluanunclassified